PENDIDIKAN GRATIS DI ERA KAPITALIS DALAM USAHA PEMERATAAN HAK ATAS PENDIDIKAN - Permatasari, Anggi Novella; Syafi’i, Imam (Universitas Tanjungpura, 2022)
Education is the right of everyone to get the opportunity to develop their potential through a process called learning which is said to be able to break the chain of poverty. However, has the implementation of this statement been running properly in Indonesia? That every citizen has the same rights in the form of the opportunity to attend school to university? Is